STUDI KOMPARASI HASIL BELAJAR PEMBELAJARAN MATEMATIKA MENERAPKAN MODEL NHT DAN JIGSAW DI KELAS IV - Maisyarah, Siti; Tampubolon, Budiman; Sabri, Tahmid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to analyze the presence or absence of significant differences. The two average learning outcomes determine the circumference and area of a simple flat building between learning taught using the Numbered Head Together (NHT) type of cooperative learning model and those taught using the Jigsaw cooperative learning model. in grade IV of Sungai Ambawang State Elementary School 29. The research method used is the experimental method with quasi-experimental design, experimental design Nonequivalent Control Group Design. The population in this study were all grade IV SDN 29 Sungai Ambawang, which consisted of two classes namely class IV A, IV B with a total of 44 students. The research sample was class IV A and class IV B, which consisted of 22 students in class IV A (experimental class 1) and 22 students in class IV B (experimental class 2). Data collection tools in the form of tests of student learning outcomes with a number of 10 essay questions. Based on the statistical calculation of the average learning outcomes of the final grade IV A test (experiment 1) of 67.5 and the average learning outcomes of the final test of class IV B (experiment 2) of 67.5 obtained tcount of 0.6122 and t table Î± = 5% (with dk = 22 + 22 - 2 = 42) of 2.0252 which means thitung (0.6122) <ttable (2.0252), then Ha is rejected. So, it can be concluded that there are no significant differences in the two average student learning outcomes in the material determining the circumference and area of simple flat building, between groups of students taught by applying the cooperative learning model Numbered Head Together, and the group of students taught by applying type Jigsaw in grade IV SDN 29 Sungai Ambawang.Â Keywords: Comparative study, Numbered Head Together, Jigsaw